Inhibition of Cdk2 kinase activity selectively targets the CD44/CD24 stem-like subpopulation and restores chemosensitivity of SUM149PT triple-negative breast cancer cells - Opyrchal, Mateusz; Salisbury, Jeffrey L.; Iankov, Ianko; Goetz, Matthew P.; McCubrey, James A.; Gambino, Mario W.; Malatino, Lorenzo; Puccia, Giuseppe; Ingle, James N.; Galanis, Evanthia; D'Assoro, Antonino B. (My University, 2014)
Inflammatory breast cancer (IBC) is an angioinvasive and most aggressive type of advanced breast cancer characterized by rapid proliferation, chemoresistance, early metastatic development and poor prognosis. IBC tumors display a triple-negative breast cancer (TNBC) phenotype characterized by centrosome amplification, high grade of chromosomal instability (CIN) and low levels of expression of estrogen receptor α (ERα), progesterone receptor (PR) and HER-2 tyrosine kinase receptor. Since the TNBC cells lack these receptors necessary to promote tumor growth, common treatments such as endocrine therapy and molecular targeting of HER-2 receptor are ineffective for this subtype of breast cancer. To date, not a single targeted therapy has been approved for non-inflammatory and inflammatory TNBC tumors and combination of conventional cytotoxic chemotherapeutic agents remains the standard therapy. IBC tumors generally display activation of epithelial to mesenchymal transition (EMT) that is functionally linked to a CD44+/CD24−/Low stem-like phenotype. Development of EMT and consequent activation of stemness programming is responsible for invasion, tumor self-renewal and drug resistance leading to breast cancer progression, distant metastases and poor prognosis. In this study, we employed the luminal ER+ MCF-7 and the IBC SUM149PT breast cancer cell lines to establish the extent to which high grade of CIN and chemoresistance were mechanistically linked to the enrichment of CD44+/CD24low/− CSCs. Here, we demonstrate that SUM149PT cells displayed higher CIN than MCF-7 cells characterized by higher percentage of structural and numerical chromosomal aberrations. Moreover, centrosome amplification, cyclin E overexpression and phosphorylation of retinoblastoma (Rb) were restricted to the stem-like CD44+/CD24−/Low subpopulation isolated from SUM149PT cells. Significantly, CD44+/CD24−/Low CSCs displayed resistance to conventional chemotherapy but higher sensitivity to SU9516, a specific cyclin-dependent kinase 2 (Cdk2) inhibitor, demonstrating that aberrant activation of cyclin E/Cdk2 oncogenic signaling is essential for the maintenance and expansion of CD44+/CD24−/Low CSC subpopulation in IBC. In conclusion, our findings propose a novel therapeutic approach to restore chemosensitivity and delay recurrence of IBC tumors based on the combination of conventional chemotherapy with small molecule inhibitors of the Cdk2 cell cycle kinase.
Keywords: breast cancer; metastases; cell cycle; cancer stem cells; cyclin E; centrosome amplification; chromosomal instability